Attitude and practices among nurses regarding oral health care of nonambulatory patients in hospitals of Warangal city - Telangana, India - M Monica; Yadav Rao Koppula; P Parthasarathi Reddy; Shakeel Anjum; A Sheetal; Nitish Pagatur (Journal of Indian Association of Public Health Dentistry, 2017)
Introduction: Dental care for chronically ill and nonambulatory patients has an impact on the clinical outcomes and well-being. Poor oral care can result in nutritional deficiency, infections and can have an adverse effect on quality of life. Hence, oral hygiene of these patients is a basic responsibility of nurses. Aim: This study aims to assess the attitudes and practices among nurses regarding the oral health care of nonambulatory patients in hospitals of Warangal city, Telangana. Materials and Methods: A descriptive cross-sectional study was conducted at five private and one government hospitals of Warangal city, Telangana. Data were collected among 208 nurses using pretested self-administered questionnaire regarding attitude and practices of nurses toward oral health care of nonambulatory patients. Responses were coded and analyzed using Statistical Package for the Social Sciences version 20. Results: Majority of the nurses (45.2%) stated that trained nurses carry out the oral care in wards. About 53.8% nurses reported that uncooperative patients hinder them in performing oral care, 47% considered cleaning the oral cavity of the patients as an unpleasant task, and 70.2% nurses felt that checking the oral cavity and its status of the patient is their responsibility. Conclusion: Practices and attitudes of nurses on oral health care toward nonambulatory patients are found to be satisfactory.